Evaluación del proceso para la obtención de un biolubricante partiendo de residuos de aceites de cocina para una empresa dedicada al tratamiento de aceites (2020)
The purpose of this work was to use a used cooking oil (ACU) from a restaurant in Bogotá D.C for the study of the production of a biolubricant, through experimental development to find the best Operating conditions. Prior to the experimental development, a characterization of the raw material where it was evidenced by tests such as gas-mass chromatography, acid number, peroxide index, viscosity, among others that the sample analyzed is a mixture of oils that presented a high amount of oleic acid and palmitic acid; with those amounts in your composition and test results it was determined that the sample It resembled its behavior to a sunflower oil. Subsequently, it was compared experimentally and bibliographically obtaining the lubricant through two processes of synthesis (double stage of transesterification and enzymatic hydrolysis) where it was varied the type of catalyst to use; in the first one a basic catalyst, hydroxide, was used potassium (KOH), and in the second an enzymatic catalyst (Lipase) was used Aspergillius genetically modified).